2021
DOI: 10.3390/ph14111194
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Propylthiouracil and Its N-β-d Glucuronide by HPLC-MS/MS: Application to a Metabolic Study

Abstract: Propylthiouracil (PTU) is commonly prescribed for the management of hyperthyroidism and thyrotoxicosis. Although the exact mechanism of action is not fully understood, PTU is associated with hepatoxicity in pediatric population. Glucuronidation mediated by uridine 5′-diphospho-glucuronosyltransferases (UGTs), which possess age-dependent expression, has been proposed as an important metabolic pathway of PTU. To further examine the metabolism of PTU, a reliable HPLC-MS/MS method for the simultaneous quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The poor metabolic stability of BTL-I is a significant limitation in terms of its pharmacokinetic properties. It was observed that the methyl ester group of BTL-I is crucial for its rapid metabolism, which was confirmed through in vitro metabolic profiles and similar metabolic half-lives in human liver microsomes (HLM) with different enzymatic cofactors (Figure A). The t 1/2 of BTL-I in HLM with nicotinamide adenine dinucleotide phosphate (NADPH) and uridine diphosphate glucuronic acid (UDPGA) were 19.58 and 17.54 min, respectively, similar to that in HLM without cofactors ( t 1/2 = 16.99 min). These findings suggest that the methyl ester moiety of BTL-1 serves as the primary metabolic site for carboxylesterases, with BTL-1 primarily cleared through esterase metabolism, while metabolism by cytopigments (CYPs) and UGTs is minimal.…”
Section: Results and Discussionmentioning
confidence: 57%
“…The poor metabolic stability of BTL-I is a significant limitation in terms of its pharmacokinetic properties. It was observed that the methyl ester group of BTL-I is crucial for its rapid metabolism, which was confirmed through in vitro metabolic profiles and similar metabolic half-lives in human liver microsomes (HLM) with different enzymatic cofactors (Figure A). The t 1/2 of BTL-I in HLM with nicotinamide adenine dinucleotide phosphate (NADPH) and uridine diphosphate glucuronic acid (UDPGA) were 19.58 and 17.54 min, respectively, similar to that in HLM without cofactors ( t 1/2 = 16.99 min). These findings suggest that the methyl ester moiety of BTL-1 serves as the primary metabolic site for carboxylesterases, with BTL-1 primarily cleared through esterase metabolism, while metabolism by cytopigments (CYPs) and UGTs is minimal.…”
Section: Results and Discussionmentioning
confidence: 57%
“…Related studies have reported that glucuronidation mediated by uridine 50-diphospho-glucuronosyltransferases (UGTs) has been proposed as a potential metabolic pathway of PTU. In vitro experiments showed that the UGT1A9 inhibitor (magnolol) significant inhibition of PTU metabolism when the concentrations of various subtypes of UGTs enzyme inhibitors were 10 μM and 50 μM ( Li et al, 2021 ). Therefore, we tried to simulate the disposition process using UGT1A9 as the main metabolic enzyme.…”
Section: Discussionmentioning
confidence: 99%